Pathogenic Leptospira isolated from rodents in New Orleans, Louisiana USA, and associated site information - Peterson, Anna; Blum, Michael; Ghersi, Bruno; Riegel, Claudia; Wunder, Elsio; Childs, James (Zenodo, 2020)
Land use change can elevate disease risk by creating conditions beneficial to species that carry zoonotic pathogens. Observations of concordant global trends in pathogen prevalence and disease incidence have engendered concerns that urbanization could increase transmission risk of some pathogens. Yet host-pathogen relationships underlying transmission risk have not been well characterized within cities, even where contact between humans and species capable of transmitting pathogens of concern occur. We addressed this deficit by testing the hypothesis that areas in cities experiencing greater population loss and infrastructure decline (i.e., counter-urbanization) can support a greater diversity of host species and a larger and more diverse pool of pathogens. We did so by characterizing pathogenic Leptospira infection relative to rodent host richness and abundance across a mosaic of abandonment in post-Katrina New Orleans (Louisiana, USA). We found that Leptospira infection loads were highest in areas that harbored higher rodent species richness. Areas with greater host co-occurrence also harbored a greater number of hosts, including the most competent hosts, indicating that Leptospira infection is amplified by increases in overall and relative host abundance. Evidence of shared infection among rodent hosts indicates that cross-species transmission of Leptospira likely increases infection at sites with greater host syntopy. Additionally, evidence that rodent co-occurrence and abundance and Leptospira infection load parallel abandonment suggests that counter-urbanization can elevate zoonotic disease risk within cities, particularly in underserved communities that are burdened with disproportionate concentrations of derelict properties. Information explaining each column is included in the metadata tab. Environmental data is only included for the subset of sites at which we targeted rats and mice (as explained in the manuscript). Data for every animal tested for Leptospira is included in the Leptospira tab. Not ...